The therapeutic potential of synthetic human atrial natriuretic peptide in nephrotic syndrome: a randomized controlled trial - Kanzaki, Motoko (Dove Medical Press, 2012)
BACKGROUND: In nephrotic syndrome, the combination of furosemide and albumin infusion is a standard regimen to treat systemic edema. The efficacy of synthetic human atrial natriuretic peptide (hANP) for nephrotic syndrome to ameliorate the systemic edema and retain renal functions has not been fully demonstrated. TRIAL DESIGN: We conducted a prospective, randomized, controlled, open-label clinical trial. Patients were randomly assigned by a stratified biased coin design. METHODS: A total of 12 patients with nephrotic syndrome between the ages of 20 to 79 years were enrolled and randomly assigned to either the conventional (CON) group treated with furosemide and albumin, and hANP group, in which carperitide was administered in addition to the conventional therapies. The primary end points were: (1) the differences in serum creatinine levels, and (2) the reduction of total dosage of furosemide and albumin by the treatments of hANP. Secondary end points were body weight, systolic blood pressure, heart rate, serum protein, albumin, and urinary protein excretion. RESULTS: A total of 13 patients were enrolled, and one patient was excluded due to severe pneumonia. In both hANP (n = 7) and CON (n = 5) groups, body weight was reduced after 2-week treatments. Serum creatinine levels at follow-up significantly increased compared with baseline. The increase in serum creatinine levels (Δ serum creatinine) was smaller in the hANP group compared with the CON group (P = 0.31). The serum uric acid, serum urea nitrogen, and urinary protein excretion were reduced in the hANP group, and increased in the CON group, though these differences were not statistically significant. The usage of hANP significantly reduced the total dosage of furosemide (P < 0.05) during the treatment periods. No adverse effects were observed. CONCLUSIONS: The concomitant use of synthetic hANP with conventional therapies is beneficial for reducing the dosage of loop diuretics, and the elevation of serum creatinine and uric acid may be avoided.